The PEA-15/PED protein regulates cellular survival and invasiveness in colorectal carcinomas - Funke, Verena; Lehmann-Koch, Judith; Bickeböller, Michèle; Benner, Axel; Tagscherer, Katrin; Grund, Kerstin; Pfeifer, Marco; Herpel, Esther; Schirmacher, Peter; Chang-Claude, Jenny; Brenner, Hermann; Hoffmeister, Michael; et al. (Cancer letters, 2013)
The PEA-15/PED (phosphoprotein enriched in astrocytes 15kD/phosphoprotein enriched in diabetes) protein is a multifunctional phosphoprotein involved in various signaling pathways which determine survival, proliferation, and migration of cancer cells. Here, we investigated the expression and cellular functions of PEA-15 in colorectal carcinoma (CRC). PEA-15 is expressed in the majority of human CRC, predominantly in well differentiated tumor areas. A tissue microarray analysis of 1262 human CRC specimens from the DACHS study showed that PEA-15 expression is significantly associated with a low pT stadium as defined by limited invasion into the bowel wall. Moreover, patients with PEA-15-positive CRC exhibited a significantly longer tumor-specific survival time. To investigate the functional relevance of PEA-15 expression on a cellular level, we over-expressed PEA-15 in several CRC cell lines. Increased expression of PEA-15 resulted in a strong inhibition of clonogenicity, proliferation, and invasiveness of CRC cells. These effects were associated with a PEA-15-dependent down-regulation of integrin αvβ5 as well as with elevated levels of the phosphorylated MAP kinase ERK1/2. Moreover, expression of PEA-15 resulted in significant protection from cell death induced by cytotoxic drugs (5-FU, cisplatin), by the death ligand TRAIL, or by serum withdrawal. In conclusion, the PEA-15 protein regulates invasiveness, proliferation, and apoptosis resistance in CRC cells. PEA-15 might play an important role in chemoresistance, progression and metastasis in CRC.
Gesehen am 14.06.2021